2022
DOI: 10.1172/jci158545
|View full text |Cite
|
Sign up to set email alerts
|

TIAM1-mediated synaptic plasticity underlies comorbid depression–like and ketamine antidepressant–like actions in chronic pain

Abstract: Chronic pain often leads to depression, increasing patient suffering and worsening prognosis. While hyperactivity of the anterior cingulate cortex (ACC) appears to be critically involved, the molecular mechanisms underlying comorbid depressive symptoms in chronic pain remain elusive. T cell lymphoma invasion and metastasis 1 (Tiam1) is a Rac1 guanine nucleotide exchange factor (GEF) that promotes dendrite, spine, and synapse development during brain development. Here, we show that Tiam1 orchestrates synaptic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…Subsequently, we discovered that the DEGs were also associated with synaptic plasticity and learning or memory; meanwhile, our findings revealed that the downregulated DEGs in pulpitis were primarily involved in the immune system process and response to stimulus, while the upregulated DEGs were predominantly involved in the cell part, membrane part, binding, transcription factor activity protein binding, and cell process. Our verified results of qRT-PCR also showed that the DEGs involved in the pathway of immune response and synaptic plasticity were significantly downregulated, which was consistent with previous reports. , This suggested that pulpitis may evade the host’s immunity in the brain by inhibiting the host immune system and host apoptosis of infection and may also utilize autophagy , and ATP to promote metabolic rate to control the body’s immune system. We hypothesized that these signaling pathways may occur in conjunction with synaptic plasticity changes in the brain to regulate the body’s immune system. To unravel the mechanism of pulpitis pain, further in-depth proteomic studies were warranted to substantiate our results.…”
Section: Discussionsupporting
confidence: 90%
“…Subsequently, we discovered that the DEGs were also associated with synaptic plasticity and learning or memory; meanwhile, our findings revealed that the downregulated DEGs in pulpitis were primarily involved in the immune system process and response to stimulus, while the upregulated DEGs were predominantly involved in the cell part, membrane part, binding, transcription factor activity protein binding, and cell process. Our verified results of qRT-PCR also showed that the DEGs involved in the pathway of immune response and synaptic plasticity were significantly downregulated, which was consistent with previous reports. , This suggested that pulpitis may evade the host’s immunity in the brain by inhibiting the host immune system and host apoptosis of infection and may also utilize autophagy , and ATP to promote metabolic rate to control the body’s immune system. We hypothesized that these signaling pathways may occur in conjunction with synaptic plasticity changes in the brain to regulate the body’s immune system. To unravel the mechanism of pulpitis pain, further in-depth proteomic studies were warranted to substantiate our results.…”
Section: Discussionsupporting
confidence: 90%
“…Functional synaptic plasticity is characterized by the weakening of inhibitory synapses and strengthening of excitatory synapses, and structural plasticity is characterized by an increase in the number and size of dendritic spines in excitatory synaptic regions. Previous studies have shown that T-cell lymphoma invasion and metastasis-inducing protein 1 (Tiam1) is a key factor in the pathophysiology of chronic pain-induced depressive-like behaviors and the sustained antidepressant-like effects of ketamine ( 39 ). Recent studies have shown that Tiam1–Rac1 signaling in excitatory neurons in the posterior horn of the spinal cord is involved in the occurrence, transformation, and maintenance of a variety of NP types by coordinating structural and functional synaptic plasticity ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…They confirmed the long-lasting antidepressant effect of a single injection of ketamine and observed changes in synaptic plasticity resulting from persistent changes in dendritic spines and synapse-associated proteins. Similarly, ketamine has been shown to be effective in inducing long-lasting changes in synaptic plasticity in depression-like behaviors in several models, including chronic corticosterone (CORT) associated with repetitive restraint stress [ 30 ], anxiety disorders associated with post-traumatic stress disorder (PTSD) [ 31 ], chronic pain [ 32 ], and middle cerebral artery occlusion associated with chronic unanticipated mild stress [ 33 ]. Similar experimental results have also been observed with ketamine in normal animals [ 34 , 35 ].…”
Section: Synaptic Plasticity Participated In Sustained Antidepressantmentioning
confidence: 99%